MANAJEMEN LITBANG DI PERGURUAN TINGGI: UPAYA MEWUJUDKAN RESEARCH UNIVERSITY - Hidayat, Dudi (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2008)
Universities in general can be categorized into three types. The first type is the Teaching University where teaching becomes the major activity without significant research activities. The Second type is the Research University where in addition to teaching activities, it carries out significant research activities. In this type of University, research is the major concern of all civitas academica. The third type is the Entrepreneurial University where it uses its research capacity to collaborate with industries or even creates its own technology-based companies. The history of European universities has shown that it has evolved from teaching university into research university, and then from research university into entrepreneurial university. The majority of universities in Indonesia are teaching universities. Becoming a research university is a desire of most Indonesian Universities. The desire is a must if universities are tocontribute to the national economic growth. A successful collaboration with industry can only be carried out by universities that have a good research capacity. This paper describes the research results concerning the practice of research and development (R&D) management in several universities in Indonesia. Using the analytical framework of effective R&D management practice, it analyses the management practice in several departments ina number of Indonesian universities that relatively has a better scientific productivity compared to other universities. The analysis showed that Indonesian universities can suitably be classified as Teaching Universities. Its R&D management practices are still littered with serious problems.